2008
DOI: 10.1097/sap.0b013e3181238dd7
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Keloid Growth Pattern and Stretching Tension

Abstract: These stretching results have advanced understanding of keloid formation under various conditions. Our results suggest that stretching tension is an important condition associated with keloid growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(97 citation statements)
references
References 15 publications
2
95
0
Order By: Relevance
“…The tape-based device showed better isolation from shear across the incision compared to staples and sutures, holding the wound intact and keeping the strains uniform along the incision. This would lead to better wound healing and reduced scarring [10-11]. …”
Section: Resultsmentioning
confidence: 99%
“…The tape-based device showed better isolation from shear across the incision compared to staples and sutures, holding the wound intact and keeping the strains uniform along the incision. This would lead to better wound healing and reduced scarring [10-11]. …”
Section: Resultsmentioning
confidence: 99%
“…21,50,58,87,88 This is supported by the increased incidence of abnormal scar formation in areas subject to the most movement, such as the scapular region and chest. 69,89,90 Minimization of movement over these areas has been shown to reduce the degree of abnormal scarring. 73,83,91,92 A number of investigations have found that mechanical force on wounds, particularly cyclical force, stimulates the release of growth factors such as TGF-β.…”
Section: Mechanical Stress and Scarringmentioning
confidence: 99%
“…45 In addition, the characteristic shapes of keloid scars, namely, the butterfly, crab’s claw, and dumbbell shapes, are largely determined by the direction of the local mechanical forces on the skin. 46 Our previous review has described the potential molecular signaling pathways behind this phenomenon. 47 …”
Section: Hypotheses On the Etiology Of Pathological Scarringmentioning
confidence: 99%